Mastering Machine Learning on AWS : Advanced machine learning in Python using SageMaker, Apache Spark, and TensorFlow /: Advanced machine learning in Python using SageMaker, Apache Spark, and TensorFlow. (2019) - Dr, Mengle, Saket S.R; Gurmendez, Maximo
No abstract available